Simone Weil : thinking poetically - Dargan, Joan (SUNY series, Simone Weil studies., 1999)
"Simone Weil created a memorable oeuvre remarkable for its lucid, striking, and seemingly transparent prose. The first to recognize Weil's achievement as a writer, this book situates her work within the French literary tradition, showing its affinities with Pascal and Baudelaire, and acknowledges its kinship to the works of poets and writers of her generation, notably the poets Rene Char and Marina Tsvetaeva. Close reading of passages from her notebooks, several short texts, and a proposal for front-line nurses addressed to the Free French illustrates the forces and influences at work in her writing."--Jacket